2012
DOI: 10.1002/smj.2022
|View full text |Cite
|
Sign up to set email alerts
|

Business model innovation and competitive imitation: The case of sponsor‐based business models

Abstract: This paper provides the first formal model of business model innovation. Our analysis focuses on sponsor-based business model innovations where a firm monetizes its product through sponsors rather than setting prices to its customer base. We analyze strategic interactions between an innovative entrant and an incumbent where the incumbent may imitate the entrant's business model innovation once it is revealed. The results suggest that an entrant needs to strategically choose whether to reveal its innovation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
371
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(428 citation statements)
references
References 66 publications
6
371
0
9
Order By: Relevance
“…This holds also true for eBay as both revenues and profits of the marketplace section were growing at the time the management decided to build up eBay classifieds. In addition, our findings are in line with Casadesus-Masanell and Zhu (2013) who found that incumbents (in our case eBay) will react to threats to their core business by competitors. Second, our analysis supports Markides and Charitou (2004) by confirming that competing with dual business models can create great rewards in terms of additional revenues and competitive advantages for the entire firm.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This holds also true for eBay as both revenues and profits of the marketplace section were growing at the time the management decided to build up eBay classifieds. In addition, our findings are in line with Casadesus-Masanell and Zhu (2013) who found that incumbents (in our case eBay) will react to threats to their core business by competitors. Second, our analysis supports Markides and Charitou (2004) by confirming that competing with dual business models can create great rewards in terms of additional revenues and competitive advantages for the entire firm.…”
Section: Discussionsupporting
confidence: 91%
“…He therefore suggests focusing on the strategic health of a company, as the short term financial health might not be a good measurement for BMI decisions. As indicated in Figure 1, in response to innovative competitors that threaten their core business, incumbents will react by either incrementally adjust or radically innovate their business models, which might lead to operating dual business models (Casadesus-Masanell and Zhu, 2013). However, there are significant trade-offs, that make it difficult for established firms to respond to disruptive innovations effectively.…”
Section: Dual Business Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that technological change [71] and new capabilities [30] enable the development of new BM. "Know-how and SB solutions of architects and designers" (TL2) is ranked as the fourth important factor.…”
Section: Technology and Industrymentioning
confidence: 99%
“…Despite growing popularity, business model research area attracts academic exploration as according to , this area resides somewhere between economics and business strategy and more elaborated research is needed. The related area is business model innovation, which according to , remains "a slippery construct to study" (Casadesus-Masanell & Zhu, 2013). Within our research context, it is considered that platforms bring new opportunities for value creation and capture, and companies need to rethink their business model logic.…”
Section: Business Implications Of Digital Platformsmentioning
confidence: 99%